Lethal and Sublethal Effects of Conventional and Organic Insecticides on the Parasitoid Trissolcus japonicus, a Biological Control Agent for Halyomorpha halys - Ribeiro, Arthur V.; Holle, Sarah G.; Hutchison, William D.; Koch, Robert L. (Frontiers in Insect Science, 2021)
The egg parasitoid Trissolcus japonicus is a natural enemy of Halyomorpha halys, a polyphagous invasive pest in Europe and North and South America. Integration of chemical and biological control tactics could facilitate effective and sustainable integrated pest management programs. This study was conducted to assess i) the lethal effects of field rates, ii) the sublethal effects of maximum and half field rates, and iii) the lethal effects of different routes of exposure of three organic and two conventional insecticides against T. japonicus. Maximum field rates of spinosad and sulfoxaflor resulted in acute lethal toxicity to adult T. japonicus one week after residual contact exposure. Maximum and half field rates of pyrethrins, the mixture of azadirachtin and pyrethrins, and clothianidin caused sublethal effects to female wasps through residual contact exposure. Furthermore, all insecticides caused acute lethal effects one week after ingestion by unmated female wasps. Taken together, these results suggest that careful planning is necessary to ensure compatibility between biological and chemical control for H. halys. The insecticides evaluated in this study varied in toxicity to T. japonicus and should be used with caution to conserve this natural enemy for biological control of H. halys.